Analisis Tingkat Stres Kerja Relawan Organisasi Buddha: Studi Kasus di Persadabumi Medan - Dicky Paskarianto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to analyze the levels of work stress experienced by volunteers at the Persadabumi Buddhist organization in Medan, Indonesia. Volunteer work in religious organizations, while spiritually rewarding, can also be a source of psychological stress due to various organizational and individual factors. Using a quantitative descriptive approach, this research distributed a validated questionnaire to 36 active volunteers at Persadabumi Medan. The instrument consisted of 18 items measuring various dimensions of work stress including workload, time pressure, role conflict, work climate, and supervisory quality. Data analysis employed frequency distribution and stress level categorization. The results showed that 52.8% of respondents experienced low levels of work stress, 47.2% experienced moderate levels, and none experienced high levels of stress. Key stress-inducing factors identified included heavy and demanding workloads, time pressures in completing tasks, inadequate supervisory support, interpersonal conflicts, and unfavorable organizational climate. The study interprets these findings through a Buddhist psychological framework, explaining stress as a manifestation of dukkha arising from tanhā (craving) and avijjā (ignorance). Buddhist teachings on mindfulness practice (sati), the middle way (majjhima paṭipadā), right effort (sammā-vāyāma), and the importance of spiritual companionship (kalyāṇa-mitta) provide practical frameworks for stress management in volunteer contexts. The practical implications emphasize the importance of organizations providing emotionally and spiritually supportive environments, implementing balanced workload distribution, establishing realistic schedules, facilitating meditation and mindfulness practices, and strengthening social support networks among volunteers. This research contributes to understanding the intersection of organizational psychology and Buddhist philosophy in managing volunteer well-being.